2015 ISSVD, ISSWSH, and IPPS Consensus Terminology and Classification of Persistent Vulvar Pain and Vulvodynia. Issue 2 (April 2016) - Bornstein, Jacob; Goldstein, Andrew T.; Stockdale, Colleen K.; Bergeron, Sophie; Pukall, Caroline; Zolnoun, Denniz; Coady, Deborah
Abstract : Introduction: In 2014, the executive council of the International Society for the Study of Vulvovaginal Disease, the boards of directors of the International Society for the Study of Women's Sexual Health, and the International Pelvic Pain Society acknowledged the need to revise the current terminology of vulvar pain, on the basis of the significant increase in high-quality etiologic studies published in the last decade. Materials and Methods: The new terminology was achieved in the following 4 steps. The first involved a terminology consensus conference with representatives of the 3 societies, held in April 2015. Then, an analysis of the relevant published studies was used to establish a level of evidence for each factor associated with vulvodynia. The terminology was amended on the basis of feedback from members of the societies. Finally, each society's board accepted the new terminology. Results and Conclusions: In 2015, the International Society for the Study of Vulvovaginal Disease, International Society for the Study of Women's Sexual Health, and International Pelvic Pain Society adopted a new vulvar pain and vulvodynia terminology that acknowledges the complexity of the clinical presentation and pathophysiology involved in vulvar pain and vulvodynia, and incorporates new information derived from evidence-based studies conducted since the last terminology published in 2003. Abstract : In 2015, the ISSVD, ISSWSH, and IPPS adopted a new vulvar pain and vulvodynia terminology acknowledging the complexity of their etiology.